Real-world questions and concerns about disease-modifying antirheumatic drugs (DMARDs): a retrospective analysis of questions to a medicine call center - Hiba EL Masri; Samantha A. Hollingworth; Mieke van Driel; Helen Benham; Treasure M. McGuire (BMC Rheumatology, 2020)
Abstract Background Disease-modifying antirheumatic drugs (DMARDs) have transformed the treatment of numerous autoimmune and inflammatory diseases but their perceived risk of harm may be a barrier to use. Methods In a retrospective mixed-methods study, we analysed conventional (c) and biologic (b) DMARDs-related calls and compared them with rest of calls (ROC) from consumers to an Australian national medicine call center operated by clinical pharmacists from September 2002 to June 2010. This includes the period where bDMARDs became available on the Pharmaceutical Benefits Scheme, the government-subsidized prescription medicines formulary. We compared caller and patient demographics, enquiry types and motivation to information-seek for both cDMARDs and bDMARDs with ROC, using a t-test for continuous data and a chi-square test for categorical data. We explored call narratives to identify common themes. Results There were 1547 calls involving at least one DMARD. The top three cDMARD enquiry types were side effects (27.2%), interactions (21.9%), and risk versus benefit (11.7%). For bDMARDs, the most common queries involved availability and subsidized access (18%), mechanism and profile (15.8%), and side effects (15.1%). The main consumer motivations to information-seek were largely independent of medicines type and included: inadequate information (44%), wanting a second opinion (23.6%), concern about a worrying symptom (18.8%), conflicting information (6.9%), or information overload (2.3%). Question themes common to conventional and biological DMARDs were caller overemphasis on medication risk and the need for reassurance. Callers seeking information about bDMARDs generally overestimated effectiveness and focused their attention on availability, cost, storage, and medicine handling. Conclusion Consumers have considerable uncertainty regarding DMARDs and may overemphasise risk. Patients cautiously assess the benefits and risks of their DMARDs but when new treatments emerge, they tend to overestimate their effectiveness.